Hemodialysis hollow fiber membrane and preparation method thereof

By optimizing the raw material ratio and preparation process of hemodialysis membrane, the combination of polyettic polyether and polyford esters solves the high cost and quality of existing hemodialysis membrane materials, and achieves the effect of reducing costs and improving performance.

CN119368020AInactive Publication Date: 2025-01-28JIANGXI SANXIN MEDTEC

Patent Information

Application Number
CN202411960471.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hemodialysis membrane materials are costly and are prone to quality problems during large-scale production. Polyaryl esters have poor compatibility with polymers such as polyether sulfone, making it difficult to maintain mechanical properties and dialysis properties after mixing.

Method used

By optimizing the raw material ratio and preparation process, the combination of polyetherin and polyford esters is used to prepare hemodialysis hollow fiber membranes, including the preparation of the spinning solution and core liquid and the wet spinning process.

Benefits of technology

The production cost is reduced, while ensuring the excellent performance of the hemodialysis membrane, including improving water, mechanical properties, and reducing albumin screening coefficients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368020A_ABST
    Figure CN119368020A_ABST
Patent Text Reader

Abstract

The invention provides a hemodialysis hollow fiber membrane and a preparation method thereof, and belongs to the technical field of separation membranes. Raw materials of the hollow fiber membrane comprise a spinning solution and a core solution, the spinning solution comprises 5wt%-20wt% of a polymer A, 1wt%-10wt% of a polymer B, 1wt%-5wt% of a pore-foaming agent and the balance of an organic solvent; the core liquid comprises 30wt%-70wt% of an organic solvent and the balance of water; the polymer A is selected from polyether sulfone, polysulfone, polyamide, cellulose acetate or polyacrylonitrile; and the polymer B is polyarylester. The preparation method comprises the following steps: carrying out vacuum defoaming treatment on a spinning solution; the spinning solution and the core solution are spun through wet spinning, and the hollow fiber membrane is obtained after idle stroke, coagulating bath forming, water washing and drying. According to the invention, polyarylester and polyethersulfone form a bi-component polymer film-forming raw material to prepare the hemodialysis membrane, the raw material ratio and the preparation process are optimized, mutual promotion and synergism of polyarylester and polyethersulfone in the aspect of dialysis performance are realized, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of separation membranes, and particularly relates to a hemodialysis hollow fiber membrane and a preparation method thereof. Background Art

[0002] Hemodialysis technology has become the main treatment for acute and chronic renal dysfunction. Hemodialysis membrane is the most critical part of the hemodialysis process. Polysulfone, polyethersulfone, etc. have become the main materials for hemodialysis membranes because of their good biocompatibility, chemical stability, thermal stability and excellent film-forming properties.

[0003] Although the existing hemodialysis membrane materials have excellent performance, they have some problems in practical application, such as high cost and easy quality problems in large-scale production. These problems not only affect the performance of hemodialysis machines, but also increase the economic burden on patients.

[0004] Therefore, optimizing the main raw materials of hemodialysis membranes becomes the key; in addition, polymers such as polysulfone and polyethersulfone are hydrophobic and are prone to low filtration rates during hemodialysis, so auxiliary reagents are added during the production process to improve the permeability of hemodialysis membranes.

[0005] Polyarylate is a polymer membrane-forming material with advantages such as good heat resistance and wide operating temperature. It is also commonly used as a medical device. It can improve the water permeability of the membrane, but its hemodialysis performance is far inferior to that of polymers such as polyethersulfone. In addition, polyarylate has low solubility and poor compatibility with polymers such as polyethersulfone. The maximum tensile force and elongation at break of polyarylate are both low. It is difficult to maintain the mechanical properties and dialysis properties of the hollow fiber membrane after the two are mixed. In view of this, polyarylate is mostly used as the outer membrane covering layer of polyethersulfone hollow fiber membranes in hollow fiber membranes; or it is used as a porogen for the resin, and the hollow fiber membrane is obtained by extrusion and spinning after high-temperature melting above 200°C. At present, the mixed component composed of polyarylate and polyethersulfone is rarely used directly as a membrane-forming material for hollow fiber membranes. Some studies have used the mixed component for flat membranes, but in order to ensure the membrane performance, low-temperature treatment is required after membrane formation. Summary of the invention

[0006] In view of this, an object of the present invention is to provide a hemodialysis hollow fiber membrane and a preparation method thereof, aiming to solve at least one technical problem in the background technology.

[0007] The present invention is achieved in that: A hemodialysis hollow fiber membrane, wherein the raw materials of the hollow fiber membrane include spinning liquid and core liquid; The spinning solution comprises 5wt%-20wt% of polymer A, 1wt%-10wt% of polymer B, 1wt%-5wt% of porogen, and the balance is an organic solvent; The core liquid comprises 30wt%-70wt% of an organic solvent, and the remainder is water; The polymer A is selected from any one of polyethersulfone, polysulfone, polyamide, cellulose acetate and polyacrylonitrile; and the polymer B is polyarylate.

[0008] Furthermore, the usage ratio of polymer A to polymer B is ≥1.

[0009] Furthermore, the amount of polymer B is 1wt%-6wt%.

[0010] Furthermore, the spinning solution comprises 12 wt % of polymer A, 6 wt % of polymer B, 2 wt % of porogen, and the balance is organic solvent; the core liquid comprises 45 wt % of organic solvent and 55 wt % of water.

[0011] Furthermore, the spinning solution comprises 20 wt % of polymer A, 1 wt % of polymer B, 5 wt % of porogen, and the balance is organic solvent; the core liquid comprises 60 wt % of organic solvent and 40 wt % of water.

[0012] Furthermore, the porogen is selected from any one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.

[0013] Furthermore, the organic solvent is N-methylpyrrolidone or N,N-dimethylacetamide.

[0014] A second aspect of the present invention provides a method for preparing a hemodialysis hollow fiber membrane, comprising: The polymer A, polymer B and porogen in a set ratio are dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is subjected to a vacuum degassing treatment; the organic solvent is mixed with water to prepare a core liquid; The spinning solution and the core solution are spun by wet spinning, and a hollow fiber membrane is obtained after an air process, coagulation bath molding, water washing, and drying; When preparing the spinning solution, firstly dissolve part of polymer B in part of the organic solvent at 45°C-55°C under mechanical stirring, then add the remaining polymer B and organic solvent, polymer A and porogen, keep warm and continue stirring until it is completely dissolved.

[0015] Furthermore, the vacuum degassing treatment adopts a low-temperature treatment in which the spinning solution temperature is set to 5°C-RT or a heating treatment in which the spinning solution temperature is set to RT-60°C.

[0016] Compared with the prior art, the present invention can reduce costs by optimizing the raw material ratio and the preparation process while ensuring its excellent performance in hemodialysis.

[0017] The present invention adds polyarylate to the existing polymer film-forming material to form a two-component polymer to prepare a hemodialysis membrane, optimizes the raw material ratio and the preparation process, and achieves mutual promotion and synergy between the two in terms of dialysis performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The scanning electron microscope morphology image of the outer surface of the hollow fiber membrane prepared in Example 1; Figure 2 This is a scanning electron microscope morphology image of the cross section of the hollow fiber membrane prepared in Example 1. DETAILED DESCRIPTION

[0019] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] A method for preparing a hemodialysis hollow fiber membrane comprises the following steps: S1, preparation of raw materials and pretreatment; The raw materials of the hollow fiber membrane include spinning solution and core solution; wherein the spinning solution includes 5wt%-20wt% of polymer A, 1wt%-10wt% of polymer B, 1wt%-5wt% of porogen, and the balance is organic solvent; the core solution includes 30wt%-70wt% of organic solvent, and the balance is water; the organic solvent and water are mixed to obtain the core solution; The polymer A is selected from any one of polyethersulfone, polysulfone, polyamide, cellulose acetate and polyacrylonitrile; the polymer B is polyarylate (PAR); the porogen is one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol; and the organic solvent is N-methylpyrrolidone (NMP) or N,N-dimethylacetamide (DMAC).

[0021] In the following examples, the polymer A is polyethersulfone (PES), the porogen is polyvinylpyrrolidone, and the organic solvent is N-methylpyrrolidone, but the organic solvent is not limited to the above reagents, and other unlisted reagents are also applicable.

[0022] First, weigh the raw materials in proportion, dissolve part of polymer B (such as 1 / 2 weight) in part of organic solvent (such as 1 / 2 weight) at 45°C-55°C under mechanical stirring, then add the remaining polymer B and organic solvent, polymer A, and porogen, keep warm and continue stirring until they are completely dissolved to obtain a spinning solution; then vacuum degassing the solution, specifically: low-temperature vacuum degassing with the spinning solution temperature set to 5°C-RT or heating vacuum degassing with the spinning solution temperature set to RT-60°C.

[0023] The purpose of controlling the temperature and adding materials in steps when the spinning solution is dissolved is to promote the co-dissolution of polymer A and polymer B. The reason is that polymer A and polymer B have opposite temperature responsiveness. If polymer B is used in a large amount, it is more conducive to dissolution in a low temperature environment, while if polymer A is used in a large amount, it is more conducive to dissolution in a high temperature environment. In view of this, the present invention controls the ratio of the two and the dissolution steps to save dissolution time.

[0024] The dosage of polymer A and polymer B is inversely proportional, and the more polymer A is used, the less polymer B is used. Specifically, the dosage of solid content (polymer A + polymer B + porogen) is preferably 14wt%~26wt%. It has been found that when the amount of polymer film-forming material is too small, the insufficient solid content is not conducive to forming; when the amount of polymer film-forming material is too high, it is not conducive to dissolution; the increase in the amount of polymer A inhibits water permeability to a certain extent, and the increase in the amount of polymer B promotes the increase of water permeability, and the addition of a certain amount of polymer B is conducive to reducing the albumin screening coefficient; however, when the amount of polymer B exceeds that of polymer A, that is, the excessive amount of polyarylate is easy to cause instability of the hollow fiber membrane system, which makes the albumin screening coefficient rise sharply, and then the present invention limits the dosage ratio of polymer A to polymer B to ≥1. In a specific implementation, the amount of polymer B is preferably 1wt%-6wt%.

[0025] S2. The spinning solution and the core solution are spun by wet spinning; the inner diameter of the hollow fiber after spinning is controlled to be 170 μm-320 μm, and the wall thickness is controlled to be 30 μm-120 μm.

[0026] S3, after spinning, through an air process, coagulation bath molding, water washing and drying, a hollow fiber membrane is obtained; During the idle phase, the ambient humidity is controlled at 50%-100% and the idle altitude is 20 cm-100 cm. Coagulation bath molding is specifically: staying in flowing purified water at 40℃-70℃ for 5s-30s; The water washing is specifically as follows: washing with water for 180s-600s at 50°C-85°C to remove the porogen and residual organic solvent; The drying process is as follows: drying at 60°C-120°C for 180s-600s, and setting ion wind to eliminate static electricity.

[0027] Example 1 This embodiment 1 is a method for preparing a hemodialysis hollow fiber membrane, and the steps include: S1, preparation of raw materials and pretreatment; Weigh spinning solution raw materials according to 12wt% polyethersulfone, 6wt% polyarylate, 2wt% polyvinylpyrrolidone, and 80wt% N-methylpyrrolidone, and first add 1 / 2 weight of polyarylate and 1 / 2 weight of N-methylpyrrolidone to completely dissolve under stirring conditions of 45°C and 95 rpm, then add polyethersulfone, the remaining 1 / 2 of polyarylate, the remaining 1 / 2 of N-methylpyrrolidone and polyvinylpyrrolidone to continue dissolving to obtain spinning solution; perform vacuum degassing treatment on the spinning solution at 8°C; Weigh the core liquid raw material according to 50wt% N-methylpyrrolidone and 50wt% water, and mix the two evenly to prepare the core liquid; S2, wet spinning; Based on the spinning solution and the core solution, the hollow fiber was spun using an 8-nozzle double-layer skin-core spinneret. During the spinning process, the spinning solution pressure was controlled to be set to 1000 kPa. After the spinning, the inner diameter of the hollow fiber was controlled to be about 190 μm, and the wall thickness was about 35 μm. S3, molding process; First, it was treated in the air at a height of 50 cm and a humidity of 70%, then stayed in flowing purified water at 50°C for 10 seconds for coagulation bath molding, and then washed with water at 50°C for 300 seconds to remove the porogen and residual organic solvent; finally, it was dried at 80°C for 300 seconds, and ion wind was set to eliminate static electricity. The resulting hollow fiber membrane was recorded as PEPA-1.

[0028] Example 2 This embodiment 2 is a method for preparing a hemodialysis hollow fiber membrane, and the steps include: S1, preparation of raw materials and pretreatment; Weigh spinning solution raw materials according to 20wt% polyethersulfone, 1wt% polyarylate, 5wt% polyvinylpyrrolidone, and 74wt% N-methylpyrrolidone, and first add 1 / 2 weight of polyarylate and 1 / 2 weight of N-methylpyrrolidone to completely dissolve under stirring conditions of 55°C and 105 rpm, then add polyethersulfone, the remaining 1 / 2 of polyarylate, the remaining 1 / 2 of N-methylpyrrolidone and polyvinylpyrrolidone to continue dissolving to obtain spinning solution; perform vacuum degassing treatment on the spinning solution at 50°C; Weigh the core liquid raw materials according to 60wt% N-methylpyrrolidone and 40wt% water, and mix the two evenly to prepare the core liquid; S2, wet spinning; Based on the spinning solution and the core solution, a hollow fiber was prepared by spinning using an 8-nozzle double-layer skin-core spinneret. During the spinning process, the spinning solution pressure was controlled to be set to 1200 kPa. After the spinning, the inner diameter of the hollow fiber was controlled to be about 200 μm and the wall thickness was about 40 μm. S3, molding process; First, it was treated in the air at a height of 80 cm and a humidity of 70%, then stayed in flowing purified water at 50°C for 15 seconds for coagulation bath molding, and then washed with water at 70°C for 330 seconds to remove the porogen and residual organic solvent; finally, it was dried at 100°C for 330 seconds, and ion wind was set to eliminate static electricity. The resulting hollow fiber membrane was recorded as PEPA-2.

[0029] Example 3 This embodiment 3 is a method for preparing a hemodialysis hollow fiber membrane, and the steps include: S1, preparation of raw materials and pretreatment; Weigh spinning solution raw materials according to 7.5wt% polyethersulfone, 7.5wt% polyarylate, 3wt% polyvinylpyrrolidone, and 82wt% N-methylpyrrolidone, and first add 1 / 2 weight of polyarylate and 1 / 2 weight of N-methylpyrrolidone to completely dissolve under stirring conditions of 45°C and 95 rpm, then add polyethersulfone, the remaining 1 / 2 of polyarylate, the remaining 1 / 2 of N-methylpyrrolidone and polyvinylpyrrolidone to continue dissolving to obtain spinning solution; perform vacuum degassing treatment on the spinning solution at 8°C; Weigh the core liquid raw material according to 50wt% N-methylpyrrolidone and 50wt% water, and mix the two evenly to prepare the core liquid; S2, wet spinning; Based on the spinning solution and the core solution, the hollow fiber was spun using an 8-nozzle double-layer skin-core spinneret. During the spinning process, the spinning solution pressure was controlled to be set to 1000 kPa. After the spinning, the inner diameter of the hollow fiber was controlled to be about 190 μm, and the wall thickness was about 35 μm. S3, molding process; First, it was treated in the air at a height of 50 cm and a humidity of 70%, then stayed in flowing purified water at 50°C for 10 seconds for coagulation bath molding, and then washed with water at 50°C for 300 seconds to remove the porogen and residual organic solvent; finally, it was dried at 80°C for 300 seconds, and ion wind was set to eliminate static electricity. The obtained hollow fiber membrane was recorded as PEPA-3.

[0030] Comparative Example 1 Comparative Example 1 is a method for preparing a hemodialysis hollow fiber membrane, which is different from Example 1 only in that the spinning solution raw material in S1 uses a single polyethersulfone as the membrane-forming polymer.

[0031] S1 of this comparative example 1 is: weigh out spinning liquid raw materials according to 18wt% polyethersulfone, 2wt% polyvinylpyrrolidone, and 80wt% N-methylpyrrolidone, mix and dissolve the spinning liquid raw materials under stirring conditions of 45°C and 95 revolutions per minute to obtain a spinning liquid; perform vacuum degassing on the spinning liquid at 8°C; weigh out core liquid raw materials according to 50wt% N-methylpyrrolidone and 50wt% water, and mix the two evenly to obtain a core liquid.

[0032] The other reaction steps were the same as those in Example 1, and the hollow fiber membrane finally obtained was recorded as PES-1.

[0033] Comparative Example 2 Comparative Example 2 is a method for preparing a hemodialysis hollow fiber membrane, which is different from Example 1 only in that the spinning solution raw material in S1 uses a single polyarylate as the membrane-forming polymer.

[0034] S1 of this comparative example 2 is: a spinning solution raw material is weighed according to 18wt% polyarylate, 2wt% polyvinyl pyrrolidone, and 80wt% N-methylpyrrolidone; under stirring conditions of 45°C and 95 rpm, firstly, 1 / 2 weight of polyarylate and 1 / 2 weight of N-methylpyrrolidone are added to be completely dissolved, and then the remaining 1 / 2 of polyarylate, the remaining 1 / 2 of N-methylpyrrolidone and polyvinyl pyrrolidone are added to continue to dissolve to obtain a spinning solution; the spinning solution is subjected to a vacuum degassing treatment at 8°C; a core liquid raw material is weighed according to 50wt% N-methylpyrrolidone and 50wt% water, and the two are evenly mixed to obtain a core liquid.

[0035] The other reaction steps were the same as those in Example 1, and the hollow fiber membrane finally obtained was recorded as PAR-1.

[0036] Comparative Example 3 This comparative example 3 is a method for preparing a hemodialysis hollow fiber membrane, and the steps include: S1, preparation of raw materials and pretreatment; The spinning solution raw materials are weighed according to 5wt% polyethersulfone, 10wt% polyarylate, 1wt% polyvinylpyrrolidone and 84wt% N-methylpyrrolidone, and 1 / 2 weight of polyarylate and 1 / 2 weight of N-methylpyrrolidone are first added to completely dissolve under stirring conditions of 45°C and 100 rpm, and then polyethersulfone, the remaining 1 / 2 of polyarylate, the remaining 1 / 2 of N-methylpyrrolidone and polyvinylpyrrolidone are added to continue dissolving to obtain a spinning solution; the spinning solution is subjected to vacuum degassing treatment at 8°C; Weigh the core liquid raw material according to 45wt% N-methylpyrrolidone and 55wt% water, and mix the two evenly to prepare the core liquid; S2, wet spinning; Based on the spinning solution and the core solution, the hollow fiber was spun using an 8-nozzle double-layer skin-core spinneret. During the spinning process, the spinning solution pressure was controlled to be set to 900 kPa. After the spinning, the inner diameter of the hollow fiber was controlled to be about 190 μm, and the wall thickness was about 35 μm. S3, molding process; First, it was treated in the air at a height of 20 cm and a humidity of 50%, then stayed in flowing purified water at 50°C for 10 seconds for coagulation bath molding, and then washed with water at 60°C for 330 seconds to remove the porogen and residual organic solvent; finally, it was dried at 70°C for 330 seconds, and ion wind was set to eliminate static electricity. The resulting hollow fiber membrane was recorded as PEPA-D1.

[0037] Figure 1 This is a scanning electron microscope morphology image of the outer surface of the hollow fiber membrane prepared in Example 1; Figure 2 is a scanning electron microscope morphology image of the cross section of the hollow fiber membrane prepared in Example 1; Figure 1 and Figure 2 It can be seen that the hollow fiber membrane has an asymmetric pore structure, in which the surface layer is relatively dense and serves as the main filtration layer; the inner layer has a relatively uniform sponge pore structure, which plays a supporting and filtering role.

[0038] After the hollow fiber membrane is prepared, it needs to be tested and meet the following requirements: The maximum tensile force of the hollow fiber membrane should be greater than 0.15N, and the elongation at break should be greater than 40%; The hollow fiber membrane should have a water flow rate of not less than 1000 ml / min; The hollow fiber membrane should have an albumin sieving coefficient not exceeding 0.01.

[0039] The mechanical properties, water flux and albumin screening coefficient of the hollow fiber membrane prepared by the present invention were tested, and the key dialysis performance indicators were compared with those of the existing hemodialyzer.

[0040] 1. Mechanical properties test The test equipment is a Hengyi Instrument HY-0230 tensile mechanical tester. The hollow fiber membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are used as test objects. The intact monofilament hollow fiber membranes are selected as samples, and the sample length is 80 mm. The distance between the upper and lower clamps of the input device is 50 mm, the experimental speed is set to 20 mm / min, the sample attribute is "tube (hollow fiber)", the outer diameter = 0.28 mm, the inner diameter = 0.20 mm, each test object is repeated 10 times, and the average value is taken. The results are shown in Table 1.

[0041] Table 1

[0042] It can be seen from the data in Table 1 that the hollow fiber membrane monofilament prepared in the present invention has excellent mechanical properties, and its maximum tensile force and elongation at break meet the requirements. Adding polyarylate will reduce the mechanical properties of the hollow fiber membrane.

[0043] 2. Water flow test Using purified water as the experimental liquid, the hollow fiber membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into filters for water flow test. In the present invention, water flow refers to the volume of water passing through the hollow fiber membrane per unit time. The filter was connected to the test loop, the filter was filled with purified water, the filter inlet pressure was adjusted so that the filter inlet pressure reached about 100 kPa, and the ultrafiltrate volume was measured three times after stabilization for 3 minutes, and the water flow test result was obtained after the average value was calculated; at the same time, the ultrafiltration coefficient of the filter was calculated. The ultrafiltration coefficient of the filter, kuf, refers to the number of milliliters of liquid passing through the filter per minute at a transmembrane pressure of 1 mmHg, and the unit is ml / (min·mmHg). Several commonly used dialyzers were purchased and compared with the present invention. The results are shown in Table 2.

[0044] Table 2

[0045] It can be seen from the data in Table 2 that the hollow fiber membrane monofilament prepared by the invention has excellent hydraulic permeability and its water permeability meets the requirements.

[0046] The hydraulic permeability of hollow fiber membranes PES-1 and PAR-1 prepared using single-component polymer membrane-forming materials polyethersulfone and polyarylate, respectively, is lower than that of Example 1. This shows that after the two components of polyethersulfone and polyarylate are combined in the present invention, the two play a synergistic role.

[0047] In comparative example 3, when preparing hollow fiber membrane PEPA-D1, the amount of polyethersulfone used is lower than that of polyarylate. Although its water permeability and ultrafiltration coefficient are greatly increased, it will lead to a rapid increase in dialysis rate in actual application. Too fast dialysis rate can easily cause dehydration of patients during treatment, affecting the quality of treatment.

[0048] 3. Screening coefficient test The measurement was carried out in accordance with the industry standard "YY0465-2019 Disposable Hollow Fiber Plasma Separator and Plasma Component Separator"; 1L 30g / L bovine albumin aqueous solution (ALB) was selected, the simulated blood inlet flow rate was set to 200ml / min, the filtrate flow rate was set to 30ml / min, and a circulating sample preparation mode was set to simulate the in vivo blood environment for detection and analysis. After the system was stable, samples were taken at the inlet, outlet and filtrate ends at the same time, and the ALB concentration (g / L) was determined by ultraviolet spectrophotometry. The albumin screening coefficient AUC was calculated, AUC=2×C1 / (C2+C3), C1 was the ALB concentration at the filtration end, C2 was the ALB concentration at the outlet end, and C3 was the ALB concentration at the inlet end. Several commonly used dialyzers were purchased and compared with the present invention. The results are shown in Table 3.

[0049] Table 3

[0050] In Tables 2 and 3, dialyzer A is selected from Asahi Kasei Corporation of Japan, model REXEED-15UC, batch number 7PZW12; dialyzer B is selected from Nipro Corporation of Japan, model SUREFLUX-15G, batch number 240624; dialyzer C is selected from Bain Medical Equipment (Guangzhou) Co., Ltd., model B-16HF, batch number 240802; dialyzer D is selected from Fresenius Group of Germany, model diasafeplus, batch number C7DC15100; dialyzer E is selected from Jianfan Biotechnology Group Co., Ltd., model JM-16H, batch number A2G2309C; dialyzer F is selected from Nikkiso Co., Ltd. of Taiwan, China, model EF-02, batch number 220707T5.

[0051] The albumin screening coefficient is one of the important indicators to measure the performance of the dialyzer membrane. If the albumin screening coefficient of the dialyzer is too high, it may lead to excessive albumin loss during dialysis, leading to hypoalbuminemia, increasing the risk of infection and affecting the patient's quality of life and prognosis.

[0052] It can be seen from the data in Table 3 that the hollow fiber membrane prepared in the present invention has a lower albumin screening coefficient. When preparing PEPA-1, PEPA-2 and PEPA-3, the amount of polyarylate used is not higher than that of polyethersulfone, and the albumin screening coefficient thereof is lower than that of the dialyzer commonly used on the market. When preparing PEPA-D1, the amount of polyarylate used exceeds that of polyethersulfone, which causes instability of the hollow fiber membrane system, making the albumin screening coefficient thereof higher, exceeding the requirement.

[0053] The albumin screening coefficients of hollow fiber membranes PES-1 and PAR-1 prepared using single-component polymer membrane-forming materials polyethersulfone and polyarylate, respectively, are higher than those of Example 1. This shows that after the two-component combination of polyethersulfone and polyarylate of the present invention, the two play a synergistic role.

[0054] 4. Cost Analysis Existing cost breakdown: The production cost of hollow fiber membranes mainly includes direct material cost and manufacturing overhead. The cost of a single bundle of hollow fiber membranes is determined, as shown in Tables 4 and 5 below.

[0055] Among them, Table 5 is the cost analysis of preparing hollow fiber membranes in Example 3; Table 4 is the cost analysis of polyethersulfone hollow fiber membranes. The difference between the polyethersulfone hollow fiber membrane and Example 3 is that the polyarylate therein is replaced by polyethersulfone, and its preparation method is the same as that of Example 3.

[0056] Table 4

[0057] As shown in Table 4 above, direct material costs dominate the production process, among which the cost of polymer raw materials is the highest, which is the main difficulty and breakthrough in controlling costs.

[0058] The improvement cost of the present invention is decomposed as follows: in terms of raw materials, the introduction of new materials shares more production pressure.

[0059] Table 5

[0060] According to the planned annual production of 10 million film bundles, the cost of each bundle can be reduced by 0.77 yuan, and the annual cost can be effectively saved: 7.7 million yuan. The wrapping film in Table 4 and Table 5 refers to the temporary packaging material in the production process.

[0061] From the above comparison, it can be seen that the method of the present invention can reduce production costs, thereby providing safer, more reliable, and more economical and efficient hemodialysis membrane products for clinical applications.

[0062] In summary, by optimizing the raw material ratio and the preparation process, the present invention reduces the raw material cost, thereby reducing the overall production cost, while ensuring its excellent performance in hemodialysis.

[0063] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A hemodialysis hollow fiber membrane, characterized in that: The raw materials of the hollow fiber membrane include spinning solution and core solution; The spinning solution comprises 5wt%-20wt% of polymer A, 1wt%-10wt% of polymer B, 1wt%-5wt% of porogen, and the balance is an organic solvent; The core liquid comprises 30wt%-70wt% of an organic solvent, and the remainder is water; The polymer A is selected from any one of polyethersulfone, polysulfone, polyamide, cellulose acetate and polyacrylonitrile; and the polymer B is polyarylate.

2. A hemodialysis hollow fiber membrane according to claim 1, characterized in that: The usage ratio of polymer A to polymer B is ≥1.

3. A hemodialysis hollow fiber membrane according to claim 2, characterized in that: The amount of polymer B used is 1 wt%-6 wt%.

4. A hemodialysis hollow fiber membrane according to claim 1, characterized in that: The spinning solution comprises 12 wt % of polymer A, 6 wt % of polymer B, 2 wt % of porogen, and the balance is organic solvent; the core liquid comprises 45 wt % of organic solvent and 55 wt % of water.

5. The hemodialysis hollow fiber membrane according to claim 1, characterized in that: The spinning solution comprises 20 wt % of polymer A, 1 wt % of polymer B, 5 wt % of porogen, and the balance is organic solvent; the core liquid comprises 60 wt % of organic solvent and 40 wt % of water.

6. A hemodialysis hollow fiber membrane according to any one of claims 1 to 5, characterized in that: The porogen is selected from any one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.

7. A hemodialysis hollow fiber membrane according to any one of claims 1 to 5, characterized in that: The organic solvent is N-methylpyrrolidone or N,N-dimethylacetamide.

8. A method for preparing a hemodialysis hollow fiber membrane, characterized in that: The preparation method is used to prepare a hemodialysis hollow fiber membrane according to any one of claims 1 to 7, and the preparation method comprises: The polymer A, polymer B and porogen in a set ratio are dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is subjected to a vacuum degassing treatment; the organic solvent is mixed with water to prepare a core liquid; The spinning solution and the core solution are spun by wet spinning, and a hollow fiber membrane is obtained after an air process, coagulation bath molding, water washing, and drying; When preparing the spinning solution, firstly dissolve part of polymer B in part of the organic solvent at 45°C-55°C under mechanical stirring, then add the remaining polymer B and organic solvent, polymer A and porogen, keep warm and continue stirring until it is completely dissolved.

9. The method for preparing a hemodialysis hollow fiber membrane according to claim 8, characterized in that: The vacuum degassing treatment adopts a low-temperature treatment in which the spinning solution temperature is set to 5°C-RT or a heating treatment in which the spinning solution temperature is set to RT-60°C.

Citation Information

Patent Citations

  • Adsorbent for the removal of blood cells

    CN102006899A

  • Hollow fiber membrane blood purification device

    CN105813667A

  • Blood purifier and method for producing the same

    JP2008173163A

  • High temperature corrosion reducing device for circulating fluidized bed boiler

    JP2010008043A

  • Hollow fiber blood purification membrane and method of manufacturing the same

    JP2011000145A

Cited By

  • Flat plate separation membrane for improving biocompatibility and preparation method of flat plate separation membrane

    CN120960992A